2005
DOI: 10.1162/0898929054021111
|View full text |Cite
|
Sign up to set email alerts
|

Brain Signatures of Meaning Access in Action Word Recognition

Abstract: The brain basis of action words may be neuron ensembles binding language- and action-related information that are dispersed over both language- and action-related cortical areas. This predicts fast spreading of neuronal activity from language areas to specific sensorimotor areas when action words semantically related to different parts of the body are being perceived. To test this, fast neurophysiological imaging was applied to reveal spatiotemporal activity patterns elicited by words with different action-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
273
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(311 citation statements)
references
References 28 publications
33
273
3
Order By: Relevance
“…However, the delay we used (150-200 ms) is in agreement with the beginning of motor area activation found by the magneto-encephalography study carried out by Pulvermüller et al [21] during which action verbs were presented. Nevertheless, future studies will test whether or not M1 is modulated by TMS applied at different delays after presentation of symbolic gestures and communicative words.…”
Section: Article In Presssupporting
confidence: 86%
See 1 more Smart Citation
“…However, the delay we used (150-200 ms) is in agreement with the beginning of motor area activation found by the magneto-encephalography study carried out by Pulvermüller et al [21] during which action verbs were presented. Nevertheless, future studies will test whether or not M1 is modulated by TMS applied at different delays after presentation of symbolic gestures and communicative words.…”
Section: Article In Presssupporting
confidence: 86%
“…the hand waving beginning for gesture "ciao"), and 150 ms [21] after the isolation point (i.e. the point after which it was possible to discriminate if the string of letters, was meaningful or meaningless) for videos presenting spoken words and pseudo-words.…”
Section: Article In Pressmentioning
confidence: 99%
“…Neuroimaging studies have reported activations in the motor and premotor brain regions during the comprehension of action-related language. Some of these studies found motor activation when people process action verbs presented in isolation (Hauk and Pulvermüller, 2004;Pulvermüller, 1996;Pulvermüller et al, 2005;Rizzolatti and Luppino, 2001), and others have found similar motor activation when people process action-related sentences (Aziz-Zadeh et al, 2006;Moody and Gennari, 2010;Raposo et al, 2009;Tettamanti et al, 2005;Urrutia et al, 2012;De Vega et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One of these issues is the need to determine whether language-induced motor activations are exclusively lexical or are dependent to some extent on the semantic context. One possibility is that the activation of the motor cortex occurs automatically about 150-200 ms after the onset of action verbs, as part of their lexical processing (Pulvermüller et al, 2005;Boulenger et al, 2006;Buccino et al, 2001;Nazir et al, 2008;Sato et al, 2008). Another alternative is that the activation of the motor cortex associated with reading is a non-automatic, context-dependent process, involving lexical-semantic integration across the sentence.…”
Section: Introductionmentioning
confidence: 99%
“…First attempts to identify the functional role of language-related activity in cortical motor regions have also been made by investigating the time course of this activity (Boulenger et al, 2006;Pulvermüller et al, 2005a). Using magnetoencephalography (MEG), Pulvermüller et al (2005a) revealed a short-lived somatotopic activity in motor cortex while participants were listening to face-and leg-related action words.…”
Section: Introductionmentioning
confidence: 99%